Fenomena Perselingkuhan di Era Digital: Analisis Hukum Keluarga Islam Terhadap Kasus Publik Figur di Media Sosial - Nayla Salsabila; Nathania Bernesa (JOURNAL SAINS STUDENT RESEARCH, 2026)
The development of digital technology has transformed patterns of social interaction, including relationships within family life. Infidelity, which was previously associated with physical relationships, has now expanded into the digital sphere through social media, instant messaging applications, and various online platforms. This phenomenon has created new forms of non-physical relationships that nevertheless involve emotional intimacy and violations of marital commitment. This study aims to analyze the phenomenon of digital infidelity from the perspective of Islamic family law, as well as to examine its causal factors and the legal and social implications arising in the era of social media. This research employed a qualitative method with a normative juridical approach through library research. The findings indicate that digital infidelity manifests in various forms, such as emotional cheating, intensive private communication, the use of anonymous accounts, and interactions that exceed proper boundaries through social media. The phenomenon is influenced by technological advancement, unfulfilled emotional needs, validation culture on social media, weak self-control, and changing patterns of social relations in digital society. From the perspective of Islamic family law, digital infidelity generally does not fulfill the physical elements of zina, and therefore cannot yet be fully categorized as a criminal offense under positive law. Nevertheless, such behavior is still regarded as an act approaching zina because it contradicts the values of fidelity, marital commitment, and the moral and social norms upheld in society. In addition to contributing to family conflict and marital breakdown, digital infidelity also generates broader social problems such as cyberbullying, viral exposure, and cancel culture on social media. Therefore, strengthening moral values, digital literacy, and ethical awareness in the use of social media is necessary to maintain family harmony amid the rapid development of digital technology.